Prevalence of unrecognized depression and associated factors among patients attending medical outpatient department in Adare Hospital, Hawassa, Ethiopia - Tilahune AB (Dove Medical Press, 2016)
Asres Bedaso Tilahune,1 Gezahegn Bekele,1 Nibretie Mekonnen,2 Eyerusalem Tamiru2 1School of Nursing and Midwifery, College of Medicine and Health Sciences, Hawassa University, Hawassa, Ethiopia; 2Department of Medical Case Team, Hawassa University Comprehensive Specialized Hospital, Hawassa, Ethiopia Abstract: Depression is an illness that involves the body, mood, and thoughts and that affects the way a person eats, sleeps, feels about him or herself and thinks about things. Depression is one of the most common mental disorders affecting 121 million people in the world, and it frequently goes unrecognized among patients. It is estimated that 5%–10% of the population at any given time is suffering from identifiable depression needing psychiatric or psychosocial intervention. An institution-based cross-sectional study design was implemented to determine the magnitude and associated factors of unrecognized depression among patients attending the adult medical outpatient department in Adare Hospital, Hawassa, Southern Nations, Nationalities, and Peoples’ Region, Ethiopia, among 326 patients selected using systematic random sampling technique. Data were collected using the interviewer-administered technique. A structured questionnaire was used to collect data on sociodemographic characteristics and other independent variables. Depression was assessed using the Patient Health Questionnaire 9. Data were entered and analyzed using SPSS 20. The level of significance was determined at P<0.05. About 326 patients were interviewed, of whom 186 (57.1%) were males. The mean age of participant was 34 with standard deviation of ±13.1 years. Current substance users accounted for 106 (32.5%) of the total participants. Of 326 respondents, 80 (24.5%) had significant depressive symptoms, while the detection rate of depression by the clinician was 0%. Depression was associated with female sex (adjusted odds ratio [AOR] =1.63 [1.14–2.34]), age >60 years (AOR =4.14 [1.87–9.14]), being divorced (AOR =3.13 [1.70–5.76]), and having an average monthly income <750 ETB (AOR =1.92 [1.119–3.195]). The findings of this study revealed that the prevalence of depression among patients attending general medical outpatient department was highly underrecognized and unmanaged. On the basis of these results, we recommended that health-care providers perform a thorough assessment to address common mental disorders, especially depression, and suggest that training to recognize and manage depression appropriately be given. Keywords: depression, outpatient, Adare Hospital, unrecognized, institution-based cross-sectional study